Efficient radiative cooling of low-cost BaSO4 paint-paper dual-layer thin films - Felicelli Andrea; Wang Jie; Feng Dudong; Forti Endrina; El Awad Azrak Sami; Peoples Joseph; Youngblood Jeffrey; Chiu George; Ruan Xiulin (Nanophotonics)
Many materials have been explored for the purpose of creating structures with high radiative cooling potential, such as nanocellulose-based structures and nanoparticle-based coatings, which have been reported with environmentally friendly attributes and high solar reflectance in current literature. They each have their own advantages and disadvantages in practice. It is worth noting that nanocellulose-based structures have an absorption peak in the UV wavelengths, which results in a lower total solar reflectance and, consequently, reduce radiative cooling capabilities. However, the interwoven-fiber structure of cellulose gives high mechanical strength, which promotes its application in different scenarios. The application of nanoplatelet-based coatings is limited due to the need for high volume of nanoparticles to reach their signature high solar reflectance. This requirement weakens the polymer matrix and results in more brittle structures. This work proposes a dual-layer system, comprising of a cellulose-based substrate as the bottom layer and a thin nanoparticle-based radiative cooling paint as the top layer, where both radiative cooling potential and mechanical strength can be maximized. Experimental and theoretical studies are conducted to investigate the relationship between thickness and reflectance in the top coating layer with a consistent thickness of the bottom layer. The saturation point is identified in this relationship and used to determine the optimal thickness for the top-layer to maximize material use efficiency. With the use of cotton paper painted with a 125 μm BaSO4-based layer, the cooling performance is enhanced to be 149.6 W/m2 achieved by the improved total solar reflectance from 80 % to 93 %.